THE PRICE OF THE INVESTED CAPITAL AND THE FACTORS DETERMINING IT - Kramarenko, H. O.; Bershadska, I. N. (Science and Transport Progress, 2008)
The research is devoted to the problem of economic substantiation of choice of sources of capital investments of an economic subject. The research is conducted on the basis of the detailed analysis of their structure, cost and factors affecting the cost of every source.